Electrooxidation of 2,4,6-Trichlorophenol on Glassy Carbon Electrodes Modified with Composite Ni(Oh)2-Co(Oh)2 Films - Ureta-Zanartu, M; Salazar-Gonzalez, R (Sociedad Chilena de Quimica, 2013)
Glassy carbon electrodes coated with a film of electrodeposited cobalt and nickel hydroxides were prepared in order to determine its activity to the 2,4,6-trichlorophenol (TCP) oxidation. The modified electrodes were characterized by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), X-ray photoelectron spectroscopy and Scan Electron Microscopy (SEM) with Energy Dispersive X-ray Spectroscopy (EDS). The results indicate that both hydroxides are homogeneously distributed in the electrode surface. From the viewpoint of electrochemical oxidation of TCP, the presence of cobalt and nickel hydroxides on the electrode surface (i) promotes a more complete oxidation of TCP and (ii) decreases the fouling of the electrode surface in comparison with GC and GC modified with Ni or Co separately.